Profile of adverse events in toxoplasmosis drug therapy: a review (Research, Society and Development, 2021)
This study aims to analyze the profile of adverse events (AEs) of drugs for the treatment of Toxoplasmosis. This is a review carried out through a bibliographic search in the electronic databases PubMed, SciELO, Cochrane Digital Library and LILACS. The keywords “Toxoplasmosis” AND “Drug Therapy” AND “Drug-Related Side Effects and Adverse Reactions” were used. The selection was performed by two independent reviewers and the articles were included considering the presence of retrospective studies and case reports published in the literature in Portuguese and English and without time restrictions. In total, 40 articles were found, of which 14 met the inclusion criteria. Cases of cerebral, ocular, gestational and congenital Toxoplasmosis were identified. Among these, we observed a total of 85 patients with reports of AEs due to the use of Pyrimethamine, Sulfadiazine, Spiramycin, Clindamycin, Atovaquone, Trimethoprim and Sulfamethoxazole and Sulfadoxine. Clinical reactions were in the form of skin rash (57.1%), hematological alterations (28.5%), Lyell syndromes (7.1%), Stevens-Johnson (21.4%) and DRESS (21 .4%). The prevalence of AEs related to hematological alterations was seen mainly in treatments based on Pyrimethamine + Sulfadiazine, Trimethoprim and Sulfamethoxazole; on the other hand, those associated with severe syndromes are often related to the use of Pyrimethamine + Sulfadiazine. It is important to establish a standard protocol for drug therapy for Toxoplasmosis, which does not yet exist. In addition, the need to monitor patients after drug administration is highlighted, given the possibility of the occurrence of adverse events that can represent a threat to life.